Partisipasi Politik Masyarakat Pemilih Dalam Pemilihan Umum Tahun 2019 di Kabupaten Kerinci - Karyadi Karyadi; Aldri Frinaldi (Jurusan Ilmu Administrasi Negara, 2020)
This study aims to describe the political participation of the voters in the 2019 general election in Kerinci Regency. The research method uses qualitative descriptive. The research informants were determined by purposive method. Observation techniques, interviews and documentation study techniques were selected in data collection in the field. This study found that the high political participation of the people in Kerinci Regency in choosing candidate candidates at the 2019 general election democracy party was 77.58%. However, in some places the level of political participation of the people is still low, they do not vote or do not use their right to vote in the 2019 general election.